2010
DOI: 10.1007/s00392-010-0199-6
|View full text |Cite
|
Sign up to set email alerts
|

Lack of evidence for pleiotropic effects of clopidogrel on endothelial function and inflammation in patients with stable coronary artery disease: results of the double-blind, randomized CASSANDRA study

Abstract: We conclude that the beneficial effects of short-term effects of clopidogrel on endothelial function of patients with CAD are abolished after long-term clopidogrel treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…At 22 h, in fact, when platelet inhibition with both doses reaches a comparable plateau, no significant differences in flow mediated dilation are anymore detectable in the 2 groups. More recently, the same investigators have found neither an effect of chronic clopidogrel treatment (75 mg/day for 1 month) on endothelial function nor a correlation with the degree of platelet inhibition [32]. Several differences do not allow comparisons with our study: e.g., clopidogrel loading dose was not administered, platelet reactivity was assessed with light trasmittance aggregometry, threshold chosen to evaluate low responders to clopidogrel, chronic versus acute administration.…”
Section: Platelet-endothelium Interactionmentioning
confidence: 84%
“…At 22 h, in fact, when platelet inhibition with both doses reaches a comparable plateau, no significant differences in flow mediated dilation are anymore detectable in the 2 groups. More recently, the same investigators have found neither an effect of chronic clopidogrel treatment (75 mg/day for 1 month) on endothelial function nor a correlation with the degree of platelet inhibition [32]. Several differences do not allow comparisons with our study: e.g., clopidogrel loading dose was not administered, platelet reactivity was assessed with light trasmittance aggregometry, threshold chosen to evaluate low responders to clopidogrel, chronic versus acute administration.…”
Section: Platelet-endothelium Interactionmentioning
confidence: 84%
“…Both the extent of protection and the molecular mechanisms of pharmacologic preconditioning appear to be similar to those induced by classical ischemic preconditioning [2]; as such, pharmacologic preconditioning might represent a promising approach to long-term protection in patients at risk. Similar to the endothelial effect of other drugs [18], however, the clinical relevance of this strategy is dependent on whether the protection induced can be maintained over prolonged or repeated exposure to the preconditioning stimulus. Of note, few studies have investigated whether such ''chronic'' preconditioning actually exists.…”
Section: Discussionmentioning
confidence: 97%
“…A study by Warnholtz et al [23] showed a significant, dose-dependent improvement in endothelial function during the first 22 h after administration. Ostad et al [24] followed up the result with a long-term study which failed to demonstrate any effects after 28 days of treatment. They concluded that clopidogrel has positive short-term effects that are abolished in the long term.…”
Section: Discussionmentioning
confidence: 99%